Preparation method of antibacterial anti-mite cool-feeling cotton fiber based on compounding of copper-tungsten alloy and graphene fiber as well as product and application of antibacterial anti-mite cool-feeling cotton fiber

By combining copper-tungsten alloy particles with graphene fibers into cotton fibers, the shortcomings of traditional cotton fibers in antibacterial, mite-proof and temperature control properties are solved, and the preparation of high-performance fibers is realized, which is suitable for a variety of application fields.

CN119913628AInactive Publication Date: 2025-05-02HEYE HEALTH TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510058453.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-05-02
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional cotton fibers have shortcomings in antibacterial, mite-proof and temperature control performance, which is difficult to meet the market's demand for high-performance fibers.

Method used

Copper-tungsten alloy particles are combined with graphene fibers, and copper-tungsten alloy particles are prepared by high-temperature melting, ball milling and other processes, and graphene fibers are prepared by chemical vapor deposition. Combined with wet spinning and heat treatment methods, cotton fibers with antibacterial, anti-mites and coolness functions are prepared.

Benefits of technology

It has achieved significant improvements in the antibacterial, anti-mites and cool-sensing properties of cotton fibers, while maintaining the comfort of cotton fibers. It is suitable for clothing, bedding and medical protection and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to a preparation method of antibacterial anti-mite cool-feeling cotton fiber based on copper-tungsten alloy and graphene fiber compounding and a product and application of the antibacterial anti-mite cool-feeling cotton fiber. The novel functional fiber is formed by compounding the copper-tungsten alloy particles and the graphene fiber into the traditional cotton fiber. The fiber has excellent antibacterial, anti-mite and cool properties, and keeps the softness and comfort of the cotton fiber at the same time. The preparation method of the antibacterial anti-mite cool-feeling cotton fiber based on compounding of the copper-tungsten alloy and the graphene fiber comprises preparation of copper-tungsten alloy particles, synthesis of the graphene fiber and a compound treatment process of the cotton fiber, and operation methods such as a bottom blowing technology, a spheroidal graphite method, a chemical vapor deposition method, wet spinning and heat treatment are applied. The cotton fiber composite material with excellent composite performance is prepared. The fiber can be widely applied to the fields of clothing, bedding articles, medical protection and the like, and has remarkable market potential and application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of health, and in particular to a preparation method of antibacterial and anti-mite cooling cotton fiber based on a composite of copper-tungsten alloy and graphene fiber, and a product and application thereof. Background Art

[0002] As people's requirements for quality of life continue to increase, the demand for functional fibers is also increasing. Especially in terms of antibacterial, anti-mite and comfort, the market has put forward higher requirements for fibers with specific functions. Copper tungsten alloy and graphene are widely used in various fields due to their excellent performance. Copper tungsten alloy is a material with excellent electrical conductivity and antibacterial properties. Graphene is a two-dimensional crystal composed of a single layer of carbon atoms, which has excellent thermal conductivity and cooling effect. Graphene fiber has better electrical conductivity, thermal conductivity and mechanical properties than carbon fiber, as well as the characteristics of being weavable and easy to functionalize.

[0003] In the modern textile industry, the demand for functional fibers is increasing. Traditional cotton fibers are superior in comfort, but lack antibacterial, anti-mite and temperature control properties. Cotton fiber composite materials in the prior art are prepared by combining fibers and metal alloys, but such materials are mostly used in industrial or high-tech fields and have not yet been widely used in the field of health. Summary of the invention

[0004] The purpose of the present invention is to provide an antibacterial, anti-mite and cool cotton fiber based on a composite of copper-tungsten alloy and graphene fiber and a preparation process of the new cotton fiber material. The material is composed of copper-tungsten alloy particles and graphene fiber, and has multiple functions such as antibacterial, anti-mite and cool feeling.

[0005] A method for preparing antibacterial and anti-mite cool cotton fiber based on a composite of copper-tungsten alloy and graphene fiber, comprising the following steps: (1) Preparation of copper-tungsten alloy particles: Tungsten and copper are mixed in a mass ratio of 1-3:1 and made into microparticles through processes such as high-temperature melting, gas stirring, and spheroidal graphite crushing; (2) Synthesis of graphene fibers: Graphene fibers are prepared by chemical vapor deposition, copper foil is selected as a substrate, the temperature is raised to 1000°C to 1600°C in a high-temperature tube furnace for 20-30 minutes, and inert gas nitrogen is introduced for protection, the nitrogen flow rate is set to 100-200sccm, and the reaction is carried out for 40-60 minutes; the introduction of protective gas is stopped, and carbon source gas methane and hydrogen are introduced instead, and the exhaust is cooled after maintaining for 20-30 minutes, and the substrate is removed by chemical etching, the time is controlled to be 30-60 minutes, and vacuum drying is carried out at 60-80°C for 30-60 minutes to obtain graphene fibers; (3) Composite treatment of cotton fibers: Copper-tungsten alloy particles and graphene fibers are mixed in a mass ratio of 1-2:1, and ultrasonicated at 20-40 kHz in deionized water for 30 minutes to 2 hours to ensure that the two are evenly mixed. A cotton fiber based on a composite of copper-tungsten alloy and graphene fibers is obtained by wet spinning and heat treatment.

[0006] In order to overcome the shortcomings of the existing technology, the present invention introduces a composite material of copper-tungsten alloy and graphene fiber to develop a new type of cotton fiber with antibacterial, anti-mite and cooling functions while retaining the comfort of cotton fiber. This innovation not only meets the market demand for high-performance fibers, but also provides a new material with broad application prospects for the textile industry.

[0007] Copper-tungsten alloy is a material with excellent electrical conductivity and antibacterial properties. The main components of copper-tungsten alloy include copper and tungsten, of which the mass fraction of copper is usually between 60% and 80%, and the mass fraction of tungsten is between 20% and 40%. The antibacterial property of copper mainly comes from the copper ions it releases, which can destroy the cell membrane of bacteria and inhibit the growth and reproduction of bacteria. Tungsten provides structural stability and hardness of the alloy, allowing the alloy to maintain good performance even at high temperatures.

[0008] Copper-tungsten alloy particles are prepared by mixing tungsten and copper in a certain proportion, and then melting and crushing them at high temperature. The ratio of tungsten to copper can be adjusted as needed to obtain different antibacterial properties and stability. Copper-tungsten alloy has excellent antibacterial properties. Copper ions can effectively kill bacteria, while tungsten provides structural stability for the alloy.

[0009] Preferably, the preparation of the copper-tungsten alloy particles comprises: A. Raw material preparation: Tungsten powder and copper powder are mixed into copper-tungsten composite powder according to the proportion, and the mass ratio of tungsten powder to copper powder is 1-3:1, and the mixture is ensured to be even; B Melting and stirring: The tungsten powder and copper powder are heated to a molten state in a high-temperature furnace, the temperature is set to 1800℃ to 2000℃, and inert gas nitrogen is introduced by bottom blowing technology. The uniformity of the alloy is improved by gas stirring to maintain a stable alloy liquid molten state; C Cooling and crushing: The molten alloy liquid is rapidly cooled to form a solid alloy block; a ball mill is used to crush the cooled alloy block into nano-scale particles with a diameter between 50nm and 500nm, so as to facilitate compounding with cotton fibers.

[0010] Among them, during the melting process, the bottom blowing technology is used to improve the uniformity of the alloy through gas stirring. The inert gas nitrogen is used for bottom blowing from bottom to top for strong stirring. The tungsten powder and copper powder are evenly mixed at high temperature, which can accelerate the formation of a molten state.

[0011] Furthermore, the preparation and pulverization process of the copper-tungsten alloy particles is as follows: in a ball mill, a ball milling medium and a grinding ball are added, wherein the ball milling medium is a volatile organic solvent ethanol, which accounts for 5-10% of the mass of the copper-tungsten composite powder; the mass ratio of the grinding ball to the copper-tungsten composite powder is 50-60:1; the ball mill is filled with protective gas nitrogen, the circulating cooling water of the ball mill is turned on, and the ball milling is started. The ball milling time is 50-100 hours. After the ball milling is completed, the powder is allowed to stand, and the powder is taken out after the powder and the grinding balls are fully cooled to obtain a nano-scale copper-tungsten alloy powder.

[0012] Graphene is a two-dimensional crystal composed of a single layer of carbon atoms. It has excellent thermal conductivity and cooling effect. It can effectively regulate body temperature and improve the comfort of the fiber when used in bedding. Graphene fiber is synthesized by chemical vapor deposition, and the diameter of the graphene fiber is controlled between 1μm-10μm, which can ensure its good composite property with cotton fiber.

[0013] Graphene fiber is a macroscopic fibrous aggregate assembled with graphene as the main structural unit. It refers to a macroscopic assembled material mainly constructed with graphene units tightly and orderly arranged along the axial direction. Therefore, in theory, it has better electrical, thermal and mechanical properties than carbon fiber. With its excellent electrical, thermal and mechanical properties, as well as its weavable and easy functionalization characteristics, graphene fiber has gradually developed into a "star material" in the field of functional fibers.

[0014] Different from the traditional preparation process, the preparation of graphene fiber uses graphene oxide as a precursor and is extruded into filaments from the solution phase by wet spinning. The chemical vapor deposition method used in the present invention is a technology that decomposes carbon-containing compounds through chemical reactions at a relatively high temperature, and then allows graphene to grow on a substrate. The principle of chemical vapor deposition of graphene is: a carbon-containing gaseous substance is introduced into a furnace under a high temperature and high vacuum environment with hydrogen as a reducing gas to generate graphene. The graphene preparation method of the present invention is to form a transition metal film on the surface of a metal copper substrate, use this film as a catalyst, then use methane as a carbon source, and use a gas phase dissociation method to dissociate the transition metal film, so that graphene sheets are gradually formed on the surface of the transition metal film, and finally a corrosive acidic solution is used to treat the metal film, thereby preparing graphene fibers. This method can prepare large-area, high-quality, and good physical performance graphene sheets, and is an industrialized preparation method. Different from the preparation method of the existing process, the present invention uses methane as the carbon source gas and hydrogen as the reducing gas at the same time, and heats and deposits on a clean copper foil substrate under high temperature heating of 1000°C to 1600°C. The graphene film prepared by the present invention using this method has good controllability in terms of the number of layers, crystal domain size, etc., effectively improves the quality of graphene in the graphene fiber material and the composite stability of the graphene composite fiber, and greatly simplifies the preparation process of the graphene fiber material, which is a good basis for industrial production.

[0015] The present invention applies chemical vapor deposition technology to the preparation of graphene fibers, which can avoid the complicated graphene oxide reduction process in the spinning process, simplify the preparation process, and help to achieve batch preparation of graphene fibers. At the same time, it can also draw on the preparation experience of graphene films and achieve effective regulation of graphene quality by adjusting the precursor carbon source, introducing atomic doping, etc.

[0016] Preferably, the synthesis of the graphene fiber comprises: A. Heating deposition: Select copper foil as the substrate, wash it with deionized water to remove surface impurities, and then put it into a high-temperature tube furnace and heat it to 1000°C to 1600°C within 20-30 minutes, and introduce inert gas nitrogen for protection, and the nitrogen flow rate is set to 100-200sccm; when the temperature in the furnace stabilizes at the target temperature, stop introducing the protective gas, and instead introduce carbon source gas methane and hydrogen, and keep it for 20-30 minutes, the methane flow rate is 10-50 sccm, and the hydrogen flow rate is 100-300 sccm; B Exhaust Cooling: After the reaction is completed, the methane gas is turned off, and only the hydrogen gas is kept flowing in. The hydrogen gas is continued to be introduced to protect the graphene film from oxidation. The hydrogen gas flow rate is 100-200 sccm, and the cooling rate is controlled to be 5-10°C / min. After gradually cooling from the reaction temperature to room temperature, the hydrogen gas is turned off, and the metal foil or silicon wafer is taken out. At this time, a graphene film can be obtained on the substrate; C Etching and demolding: The substrate is removed by chemical etching, and the copper foil is etched with a dilute hydrochloric acid solution for 30-60 minutes; the etched graphene fiber is washed with deionized water for multiple times to remove residual acidic substances and metal impurities; after washing, the graphene fiber is placed in a drying oven for vacuum drying at a temperature of 60-80°C to obtain graphene fiber.

[0017] Preferably, the composite treatment of the cotton fiber comprises: A. Mixing of composite materials: Copper tungsten alloy particles and graphene fibers are mixed in a mass ratio of 1-2:1, and ultrasonic dispersion technology is used to select an ultrasonic frequency of 20-40 kHz in deionized water for 30 minutes to 2 hours to ensure that the two are evenly mixed; Composite treatment of B composite materials and cotton fibers: The cotton fiber is dissolved in a sodium hydroxide solvent system to form a spinning solution; the mixed copper-tungsten alloy particle-graphene fiber composite material is gradually added to the spinning solution, and mixed with a stirrer to ensure that the composite material and the cotton fiber are evenly distributed; the mixed spinning solution is wet-spun at room temperature of 20°C-40°C through a spinning nozzle; the wet-spun composite fiber is subjected to a coagulation bath treatment, and maintained in a dilute sodium hydroxide solution at 0°C to 20°C for 1-5 minutes, so that the composite material forms a stable structure in the fiber; CHeat Treatment: In an inert gas nitrogen protection environment, the composite material and cotton fiber are uniformly heated at a temperature of 150°C to 250°C and a time of 10 minutes to 60 minutes to obtain a cotton fiber based on a composite of copper tungsten alloy and graphene fiber.

[0018] Preferably, the composite cotton fiber can pass performance evaluation verification, including: testing and evaluating the antibacterial performance, anti-mite performance and cooling performance of the composite cotton fiber, and verifying that the product is an antibacterial, anti-mite and cooling cotton fiber based on a composite of copper-tungsten alloy and graphene fiber.

[0019] The antibacterial property test uses a bacterial culture method to test the antibacterial property of the composite cotton fiber. Common test strains include Staphylococcus aureus, Escherichia coli, etc. The present invention determines the antibacterial effect by the inhibition zone method and the colony counting method, and judges the antibacterial efficacy by testing the antibacterial rate.

[0020] The anti-mite performance test is evaluated by calculating the repellency rate. The test of the present invention is carried out under constant temperature and humidity conditions, and the repellency rate is calculated by comparing the number of live mites on the test sample and the control sample. When the repellency rate reaches 60% or more, it means that the test sample has an anti-mite effect; when it reaches 80% or more, it means that it has a strong anti-mite effect; when it reaches 90% or more, it means that it has an extremely strong anti-mite effect.

[0021] The test of the cooling performance of the present invention includes measuring the thermal conductivity and air permeability of the material to evaluate its comfort and heat dissipation effect in a hot environment. Thermal conductivity is one of the important indicators for measuring the thermal conductivity of a material. The smaller the thermal conductivity, the better the thermal insulation performance of the material. The air permeability test is performed by the human body to evaluate the woven fabric made of the composite cotton fiber material. Ten people with statistical significance are selected to evaluate the air permeability of woven fabrics of the same size, thickness and quality. The one with the higher score is the best.

[0022] Preferably, the cotton fiber contains copper-tungsten alloy particles and graphene fibers, the copper-tungsten alloy particles have a mass fraction of 0.5%-5%, a diameter of 50nm-5μm, and are evenly distributed; the graphene fibers have a diameter of 1μm-10μm, and a mass fraction of 0.1%-2%.

[0023] An application of antibacterial and anti-mite cool cotton fiber based on copper-tungsten alloy and graphene fiber composite includes: clothing, bedding or medical protection field, providing antibacterial, anti-mite and cool feeling functions.

[0024] The antibacterial and anti-mite cool cotton fiber based on the copper-tungsten alloy and graphene fiber composite of the present invention can be widely used in: 1. Clothing field: making anti-mite and antibacterial underwear, sportswear, etc. to improve wearing comfort and health; AHigh-Performance Sportswear: Apply composite cotton fibers to high-performance sportswear to provide antibacterial, anti-mite, cooling and other functions, improving sports comfort and performance; B Underwear and Underwear: Use composite cotton fibers in underwear and close-fitting garments to increase the comfort and hygiene of products and meet consumers' needs for health and comfort; 2. Bedding field: used to make antibacterial and anti-mite sheets, pillowcases, etc. to improve sleep quality; ABed Sheets and Quilt Covers: Apply composite cotton fibers to bed sheets and quilt covers to improve their antibacterial, anti-mite and cooling properties, and improve sleep quality; B Pillows and Mattresses: Use composite cotton fibers in pillows and mattresses to increase the comfort and health performance of the products and provide users with a better sleeping experience; 3. Medical protection field: used to make medical clothing or protective gear with antibacterial function to provide better protection; AMedical textiles: Apply composite cotton fibers to medical textiles, such as surgical gowns, mattresses, etc., to provide antibacterial and anti-mite functions and enhance the sanitary conditions of the medical environment; B Health Care Products: Composite cotton fibers are used in health care products, such as waist belts, knee pads, etc., to provide comfortable protection and protective functions.

[0025] In summary, the present invention has the following beneficial effects:

[0026] 1. This invention is the first to combine copper-tungsten alloy particles and graphene fibers into cotton fibers, combining the antibacterial properties of copper and the cooling properties of graphene to form a new type of highly functional cotton fiber; 2. Compared with the traditional process, the present invention adopts advanced mixing and compounding technology to ensure the uniform distribution of copper-tungsten alloy particles and graphene fibers in cotton fibers, thereby improving the overall performance of the fibers; 3. Compared with traditional cotton fibers, the composite cotton fibers of the present invention have significant advantages in antibacterial, anti-mite and cool feeling, while maintaining the comfort of cotton fibers; 4. The present invention uses copper-tungsten alloy and graphene as functional materials, which meet environmental protection and health standards, are harmless to the human body, and can provide users with a safe and comfortable use experience; 5. The cotton fiber with antibacterial, anti-mite, cooling and other functions prepared by the present invention can be widely used in clothing, bedding, medical protection and other fields to meet the market demand for high-performance textiles. DETAILED DESCRIPTION

[0027] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by the patent law.

[0028] Example 1

[0029] (1) Preparation of copper-tungsten alloy particles: A. Raw material preparation: Mix tungsten powder and copper powder into copper-tungsten composite powder in proportion, with the mass ratio of tungsten powder to copper powder being 7:3, and ensure that the mixture is even; B. Melting and stirring: Heat tungsten powder and copper powder to a molten state in a high-temperature furnace, set the temperature to 2000°C, introduce inert gas nitrogen by bottom blowing technology, and improve the uniformity of the alloy through gas stirring to maintain a stable alloy liquid molten state; C Cooling and crushing: The molten alloy liquid is rapidly cooled to form a solid alloy block; the solid alloy block is put into a ball mill, in which ethanol is added as a ball milling medium accounting for 7.5% of the mass of the copper-tungsten composite powder, and grinding balls are added, with a mass ratio of 55:1 to the copper-tungsten composite powder; nitrogen is filled into the ball mill as a protective gas, the circulating cooling water of the ball mill is turned on, and ball milling is started. The ball milling time is 72 hours. After the ball milling is completed, the powder is left to stand until the powder and the grinding balls are fully cooled, and the powder is taken out to obtain a nano-grade copper-tungsten alloy powder.

[0030] (2) Synthesis of graphene fibers: A Heating deposition: select copper foil as the substrate, wash it with deionized water to remove surface impurities, put it into a high-temperature tube furnace and heat it to 1200℃ for 25 minutes, and introduce inert gas nitrogen for protection, and the nitrogen flow rate is set to 150 sccm; when the temperature in the furnace stabilizes at the target temperature, stop introducing the protective gas, and replace it with carbon source gas methane and hydrogen, and keep it for 25 minutes, with a methane flow rate of 30 sccm and a hydrogen flow rate of 200 sccm; B. Exhaust cooling: After the reaction is completed, the methane gas is turned off, and only hydrogen gas is kept flowing in. Hydrogen gas is continued to be introduced to protect the graphene film from oxidation. The hydrogen flow rate is 150 sccm, and the cooling rate is controlled to be 8°C / min. After gradually cooling from the reaction temperature to room temperature, the hydrogen gas is turned off, and the metal foil or silicon wafer is taken out. At this time, a graphene film can be obtained on the substrate; C. Etching and demolding: removing the substrate by chemical etching, etching the copper foil with dilute hydrochloric acid solution for 45 minutes; washing the etched graphene fiber with deionized water for several times to remove residual acidic substances and metal impurities; after washing, placing the graphene fiber in a drying oven for vacuum drying at a temperature of 70°C to obtain graphene fiber.

[0031] (3) Composite treatment of cotton fibers: A. Mixing of composite materials: Copper-tungsten alloy particles and graphene fibers were mixed in a mass ratio of 1:1, and ultrasonic dispersion technology was used to select an ultrasonic frequency of 30 kHz in deionized water for 1 hour to ensure that the two were mixed evenly; B. Composite treatment of composite material and cotton fiber: dissolving cotton fiber in a sodium hydroxide solvent system to form a spinning solution; gradually adding the mixed copper-tungsten alloy particle-graphene fiber composite material into the spinning solution, and mixing with a stirrer to ensure that the composite material and cotton fiber are evenly distributed; wet spinning the mixed spinning solution through a spinning nozzle at room temperature of 30°C; subjecting the wet-spun composite fiber to a coagulation bath treatment, and maintaining it in a dilute sodium hydroxide solution at 0°C to 20°C for 3 minutes, so that the composite material forms a stable structure in the fiber; C. Heat treatment: In an inert gas nitrogen protection environment, the composite material and cotton fiber are uniformly heated at a temperature of 200°C for 30 minutes to obtain a cotton fiber based on a composite of copper tungsten alloy and graphene fiber.

[0032] (4) Test and evaluate the antibacterial, anti-mite and cooling properties of the composite cotton fiber: Test the antibacterial rate, repellency rate, thermal conductivity and fabric feel of the composite cotton fiber.

[0033] Example 2 (1) Preparation of copper-tungsten alloy particles: A. Raw material preparation: Mix tungsten powder and copper powder into copper-tungsten composite powder in proportion, with the mass ratio of tungsten powder to copper powder being 1:1, and ensure that the mixture is even; B. Melting and stirring: Heat tungsten powder and copper powder to a molten state in a high-temperature furnace, set the temperature to 1800°C, introduce inert gas nitrogen by bottom blowing technology, and improve the uniformity of the alloy through gas stirring to maintain a stable alloy liquid molten state; C Cooling and crushing: The molten alloy liquid is rapidly cooled to form a solid alloy block; the solid alloy block is put into a ball mill, in which ethanol as a ball milling medium is added to account for 5% of the mass of the copper-tungsten composite powder, and grinding balls are added, and the mass ratio of the copper-tungsten composite powder to the copper-tungsten composite powder is 50:1; nitrogen is filled into the ball mill as a protective gas, and the circulating cooling water of the ball mill is turned on to start ball milling. The ball milling time is 50 hours. After the ball milling is completed, it is allowed to stand for a while. After the powder and the grinding balls are fully cooled, the powder is taken out to obtain a nano-grade copper-tungsten alloy powder.

[0034] (2) Synthesis of graphene fibers: A Heating deposition: copper foil was selected as the substrate, and after being washed with deionized water to remove surface impurities, it was placed in a high-temperature tube furnace and heated to 1000°C for 20 minutes, and inert nitrogen was introduced for protection, and the nitrogen flow rate was set to 100 sccm; when the temperature in the furnace stabilized at the target temperature, the introduction of protective gas was stopped, and carbon source gas methane and hydrogen were introduced instead, and maintained for 20 minutes, with a methane flow rate of 10 sccm and a hydrogen flow rate of 100 sccm; B. Exhaust cooling: After the reaction is completed, the methane gas is turned off, and only hydrogen is allowed to flow in. Hydrogen is continued to be introduced to protect the graphene film from oxidation. The hydrogen flow rate is 100 sccm, and the cooling rate is controlled to be 5°C / min. After gradually cooling from the reaction temperature to room temperature, the hydrogen is turned off, and the metal foil or silicon wafer is taken out. At this time, a graphene film can be obtained on the substrate; C. Etching and demolding: removing the substrate by chemical etching, etching the copper foil with a dilute hydrochloric acid solution for 30 minutes; washing the etched graphene fiber with deionized water for multiple times to remove residual acidic substances and metal impurities; after washing, placing the graphene fiber in a drying oven for vacuum drying at a temperature of 60°C to obtain the graphene fiber.

[0035] (3) Composite treatment of cotton fibers: A. Mixing of composite materials: Copper-tungsten alloy particles and graphene fibers were mixed in a mass ratio of 1:1, and ultrasonic dispersion technology was used to select an ultrasonic frequency of 20 kHz in deionized water for 30 minutes to ensure that the two were mixed evenly; B. Composite treatment of composite material and cotton fiber: dissolving cotton fiber in a sodium hydroxide solvent system to form a spinning solution; gradually adding the mixed copper-tungsten alloy particle-graphene fiber composite material into the spinning solution, and mixing with a stirrer to ensure that the composite material and cotton fiber are evenly distributed; wet spinning the mixed spinning solution through a spinning nozzle at room temperature of 20°C; subjecting the wet-spun composite fiber to a coagulation bath treatment, and maintaining it in a dilute sodium hydroxide solution at 0°C to 20°C for 1 minute, so that the composite material forms a stable structure in the fiber; C. Heat treatment: In an inert gas nitrogen protection environment, the composite material and cotton fiber are uniformly heated at a temperature of 150°C for 10 minutes to obtain a cotton fiber based on a composite of copper tungsten alloy and graphene fiber.

[0036] (4) Test and evaluate the antibacterial, anti-mite and cooling properties of the composite cotton fiber: Test the antibacterial rate, repellency rate, thermal conductivity and fabric feel of the composite cotton fiber.

[0037] Example 3 (1) Preparation of copper-tungsten alloy particles: A. Raw material preparation: Mix tungsten powder and copper powder into copper-tungsten composite powder in proportion, with the mass ratio of tungsten powder to copper powder being 3:1, and ensure that the mixture is even; B. Melting and stirring: Heat tungsten powder and copper powder to a molten state in a high-temperature furnace, set the temperature to 2000°C, introduce inert gas nitrogen by bottom blowing technology, and improve the uniformity of the alloy through gas stirring to maintain a stable alloy liquid molten state; C Cooling and crushing: The molten alloy liquid is rapidly cooled to form a solid alloy block; the solid alloy block is put into a ball mill, in which ethanol as a ball milling medium is added to account for 10% of the mass of the copper-tungsten composite powder, and grinding balls are added, with a mass ratio of 60:1 to the copper-tungsten composite powder; nitrogen is filled into the ball mill as a protective gas, the circulating cooling water of the ball mill is turned on, and ball milling is started. The ball milling time is 100 hours. After the ball milling is completed, it is allowed to stand for a while, and the powder is taken out after the powder and the grinding balls are fully cooled to obtain a nano-grade copper-tungsten alloy powder.

[0038] (2) Synthesis of graphene fibers: A Heating deposition: copper foil was selected as the substrate, and after being washed with deionized water to remove surface impurities, it was placed in a high-temperature tube furnace and heated to 1600°C for 30 minutes, and inert nitrogen was introduced for protection, with the nitrogen flow rate set to 200 sccm; when the temperature in the furnace stabilized at the target temperature, the introduction of protective gas was stopped, and carbon source gases methane and hydrogen were introduced instead, and maintained for 30 minutes, with a methane flow rate of 50 sccm and a hydrogen flow rate of 300 sccm; B. Exhaust cooling: After the reaction is completed, the methane gas is turned off, and only hydrogen gas is kept flowing in. Hydrogen gas is continued to be introduced to protect the graphene film from oxidation. The hydrogen flow rate is 200 sccm, and the cooling rate is controlled to be 10℃ / min. After gradually cooling from the reaction temperature to room temperature, the hydrogen gas is turned off, and the metal foil or silicon wafer is taken out. At this time, a graphene film can be obtained on the substrate; C. Etching and demolding: removing the substrate by chemical etching, etching the copper foil with a dilute hydrochloric acid solution for 60 minutes; washing the etched graphene fiber with deionized water for multiple times to remove residual acidic substances and metal impurities; after washing, placing the graphene fiber in a drying oven for vacuum drying at a temperature of 80°C to obtain the graphene fiber.

[0039] (3) Composite treatment of cotton fibers: A. Mixing of composite materials: Copper-tungsten alloy particles and graphene fibers were mixed in a mass ratio of 2:1, and ultrasonic dispersion technology was used to select an ultrasonic frequency of 40 kHz in deionized water for 2 hours to ensure that the two were mixed evenly; B. Composite treatment of composite material and cotton fiber: dissolving cotton fiber in a sodium hydroxide solvent system to form a spinning solution; gradually adding the mixed copper-tungsten alloy particle-graphene fiber composite material into the spinning solution, and mixing with a stirrer to ensure that the composite material and cotton fiber are evenly distributed; wet spinning the mixed spinning solution through a spinning nozzle at room temperature of 40°C; subjecting the wet-spun composite fiber to a coagulation bath treatment, and maintaining it in a dilute sodium hydroxide solution at 0°C to 20°C for 5 minutes, so that the composite material forms a stable structure in the fiber; C. Heat treatment: In an inert gas nitrogen protection environment, the composite material and cotton fiber are uniformly heated at a temperature of 250°C for 60 minutes to obtain a cotton fiber based on a composite of copper tungsten alloy and graphene fiber.

[0040] (4) Test and evaluate the antibacterial, anti-mite and cooling properties of the composite cotton fiber: Test the antibacterial rate, repellency rate, thermal conductivity and fabric feel of the composite cotton fiber.

[0041] Example 4 (1) Preparation of copper-tungsten alloy particles: A. Raw material preparation: Mix tungsten powder and copper powder into copper-tungsten composite powder in proportion, with the mass ratio of tungsten powder to copper powder being 1:1, and ensure that the mixture is even; B. Melting and stirring: Heat tungsten powder and copper powder to a molten state in a high-temperature furnace, set the temperature to 1800°C, introduce inert gas nitrogen by bottom blowing technology, and improve the uniformity of the alloy through gas stirring to maintain a stable alloy liquid molten state; C Cooling and crushing: The molten alloy liquid is rapidly cooled to form a solid alloy block; the solid alloy block is put into a ball mill, in which ethanol as a ball milling medium is added to account for 5% of the mass of the copper-tungsten composite powder, and grinding balls are added, and the mass ratio of the copper-tungsten composite powder to the copper-tungsten composite powder is 50:1; nitrogen is filled into the ball mill as a protective gas, and the circulating cooling water of the ball mill is turned on to start ball milling. The ball milling time is 50 hours. After the ball milling is completed, it is allowed to stand for a while. After the powder and the grinding balls are fully cooled, the powder is taken out to obtain a nano-grade copper-tungsten alloy powder.

[0042] (2) Synthesis of graphene fibers: A Heating deposition: copper foil was selected as the substrate, and after being washed with deionized water to remove surface impurities, it was placed in a high-temperature tube furnace and heated to 1600°C for 30 minutes, and inert nitrogen was introduced for protection, with the nitrogen flow rate set to 200 sccm; when the temperature in the furnace stabilized at the target temperature, the introduction of protective gas was stopped, and carbon source gases methane and hydrogen were introduced instead, and maintained for 30 minutes, with a methane flow rate of 50 sccm and a hydrogen flow rate of 300 sccm; B. Exhaust cooling: After the reaction is completed, the methane gas is turned off, and only hydrogen gas is kept flowing in. Hydrogen gas is continued to be introduced to protect the graphene film from oxidation. The hydrogen flow rate is 200 sccm, and the cooling rate is controlled to be 10℃ / min. After gradually cooling from the reaction temperature to room temperature, the hydrogen gas is turned off, and the metal foil or silicon wafer is taken out. At this time, a graphene film can be obtained on the substrate; C. Etching and demolding: removing the substrate by chemical etching, etching the copper foil with a dilute hydrochloric acid solution for 60 minutes; washing the etched graphene fiber with deionized water for multiple times to remove residual acidic substances and metal impurities; after washing, placing the graphene fiber in a drying oven for vacuum drying at a temperature of 80°C to obtain the graphene fiber.

[0043] (3) Composite treatment of cotton fibers: A. Mixing of composite materials: Copper-tungsten alloy particles and graphene fibers were mixed in a mass ratio of 2:1, and ultrasonic dispersion technology was used to select an ultrasonic frequency of 40 kHz in deionized water for 2 hours to ensure that the two were mixed evenly; B. Composite treatment of composite material and cotton fiber: dissolving cotton fiber in a sodium hydroxide solvent system to form a spinning solution; gradually adding the mixed copper-tungsten alloy particle-graphene fiber composite material into the spinning solution, and mixing with a stirrer to ensure that the composite material and cotton fiber are evenly distributed; wet spinning the mixed spinning solution through a spinning nozzle at room temperature of 40°C; subjecting the wet-spun composite fiber to a coagulation bath treatment, and maintaining it in a dilute sodium hydroxide solution at 0°C to 20°C for 5 minutes, so that the composite material forms a stable structure in the fiber; C. Heat treatment: In an inert gas nitrogen protection environment, the composite material and cotton fiber are uniformly heated at a temperature of 250°C for 60 minutes to obtain a cotton fiber based on a composite of copper tungsten alloy and graphene fiber.

[0044] (4) Test and evaluate the antibacterial, anti-mite and cooling properties of the composite cotton fiber: Test the antibacterial rate, repellency rate, thermal conductivity and fabric feel of the composite cotton fiber.

[0045] Example 5 (1) Preparation of copper-tungsten alloy particles: A. Raw material preparation: Mix tungsten powder and copper powder into copper-tungsten composite powder in proportion, with the mass ratio of tungsten powder to copper powder being 3:1, and ensure that the mixture is even; B. Melting and stirring: Heat tungsten powder and copper powder to a molten state in a high-temperature furnace, set the temperature to 2000°C, introduce inert gas nitrogen by bottom blowing technology, and improve the uniformity of the alloy through gas stirring to maintain a stable alloy liquid molten state; C Cooling and crushing: The molten alloy liquid is rapidly cooled to form a solid alloy block; the solid alloy block is put into a ball mill, in which ethanol as a ball milling medium is added to account for 10% of the mass of the copper-tungsten composite powder, and grinding balls are added, with a mass ratio of 60:1 to the copper-tungsten composite powder; nitrogen is filled into the ball mill as a protective gas, the circulating cooling water of the ball mill is turned on, and ball milling is started. The ball milling time is 100 hours. After the ball milling is completed, it is allowed to stand for a while, and the powder is taken out after the powder and the grinding balls are fully cooled to obtain a nano-grade copper-tungsten alloy powder.

[0046] (2) Synthesis of graphene fibers: A Heating deposition: copper foil was selected as the substrate, and after being washed with deionized water to remove surface impurities, it was placed in a high-temperature tube furnace and heated to 1000°C for 20 minutes, and inert nitrogen was introduced for protection, and the nitrogen flow rate was set to 100 sccm; when the temperature in the furnace stabilized at the target temperature, the introduction of protective gas was stopped, and carbon source gas methane and hydrogen were introduced instead, and maintained for 20 minutes, with a methane flow rate of 10 sccm and a hydrogen flow rate of 100 sccm; B. Exhaust cooling: After the reaction is completed, the methane gas is turned off, and only hydrogen is allowed to flow in. Hydrogen is continued to be introduced to protect the graphene film from oxidation. The hydrogen flow rate is 100 sccm, and the cooling rate is controlled to be 5°C / min. After gradually cooling from the reaction temperature to room temperature, the hydrogen is turned off, and the metal foil or silicon wafer is taken out. At this time, a graphene film can be obtained on the substrate; C. Etching and demolding: removing the substrate by chemical etching, etching the copper foil with a dilute hydrochloric acid solution for 30 minutes; washing the etched graphene fiber with deionized water for multiple times to remove residual acidic substances and metal impurities; after washing, placing the graphene fiber in a drying oven for vacuum drying at a temperature of 60°C to obtain the graphene fiber.

[0047] (3) Composite treatment of cotton fibers: A. Mixing of composite materials: Copper-tungsten alloy particles and graphene fibers were mixed in a mass ratio of 2:1, and ultrasonic dispersion technology was used to select an ultrasonic frequency of 40 kHz in deionized water for 2 hours to ensure that the two were mixed evenly; B. Composite treatment of composite material and cotton fiber: dissolving cotton fiber in a sodium hydroxide solvent system to form a spinning solution; gradually adding the mixed copper-tungsten alloy particle-graphene fiber composite material into the spinning solution, and mixing with a stirrer to ensure that the composite material and cotton fiber are evenly distributed; wet spinning the mixed spinning solution through a spinning nozzle at room temperature of 40°C; subjecting the wet-spun composite fiber to a coagulation bath treatment, and maintaining it in a dilute sodium hydroxide solution at 0°C to 20°C for 5 minutes, so that the composite material forms a stable structure in the fiber; C. Heat treatment: In an inert gas nitrogen protection environment, the composite material and cotton fiber are uniformly heated at a temperature of 250°C for 60 minutes to obtain a cotton fiber based on a composite of copper tungsten alloy and graphene fiber.

[0048] (4) Test and evaluate the antibacterial, anti-mite and cooling properties of the composite cotton fiber: Test the antibacterial rate, repellency rate, thermal conductivity and fabric feel of the composite cotton fiber.

[0049] Example 6 (1) Preparation of copper-tungsten alloy particles: A. Raw material preparation: Mix tungsten powder and copper powder into copper-tungsten composite powder in proportion, with the mass ratio of tungsten powder to copper powder being 3:1, and ensure that the mixture is even; B. Melting and stirring: Heat tungsten powder and copper powder to a molten state in a high-temperature furnace, set the temperature to 2000°C, introduce inert gas nitrogen by bottom blowing technology, and improve the uniformity of the alloy through gas stirring to maintain a stable alloy liquid molten state; C Cooling and crushing: The molten alloy liquid is rapidly cooled to form a solid alloy block; the solid alloy block is put into a ball mill, in which ethanol as a ball milling medium is added to account for 10% of the mass of the copper-tungsten composite powder, and grinding balls are added, with a mass ratio of 60:1 to the copper-tungsten composite powder; nitrogen is filled into the ball mill as a protective gas, the circulating cooling water of the ball mill is turned on, and ball milling is started. The ball milling time is 100 hours. After the ball milling is completed, it is allowed to stand for a while, and the powder is taken out after the powder and the grinding balls are fully cooled to obtain a nano-grade copper-tungsten alloy powder.

[0050] (2) Synthesis of graphene fibers: A Heating deposition: copper foil was selected as the substrate, and after being washed with deionized water to remove surface impurities, it was placed in a high-temperature tube furnace and heated to 1600°C within 30 minutes, and inert nitrogen was introduced for protection, with the nitrogen flow rate set to 200 sccm; when the temperature in the furnace stabilized at the target temperature, the introduction of protective gas was stopped, and carbon source gases methane and hydrogen were introduced instead, and maintained for 30 minutes, with a methane flow rate of 50 sccm and a hydrogen flow rate of 300 sccm; B. Exhaust cooling: After the reaction is completed, the methane gas is turned off, and only hydrogen gas is kept flowing in. Hydrogen gas is continued to be introduced to protect the graphene film from oxidation. The hydrogen flow rate is 200 sccm, and the cooling rate is controlled to be 10℃ / min. After gradually cooling from the reaction temperature to room temperature, the hydrogen gas is turned off, and the metal foil or silicon wafer is taken out. At this time, a graphene film can be obtained on the substrate; C. Etching and demolding: removing the substrate by chemical etching, etching the copper foil with a dilute hydrochloric acid solution for 60 minutes; washing the etched graphene fiber with deionized water for multiple times to remove residual acidic substances and metal impurities; after washing, placing the graphene fiber in a drying oven for vacuum drying at a temperature of 80°C to obtain the graphene fiber.

[0051] (3) Composite treatment of cotton fibers: A. Mixing of composite materials: Copper-tungsten alloy particles and graphene fibers were mixed in a mass ratio of 1:1, and ultrasonic dispersion technology was used to select an ultrasonic frequency of 20 kHz in deionized water for 30 minutes to ensure that the two were mixed evenly; B. Composite treatment of composite material and cotton fiber: dissolving cotton fiber in a sodium hydroxide solvent system to form a spinning solution; gradually adding the mixed copper-tungsten alloy particle-graphene fiber composite material into the spinning solution, and mixing with a stirrer to ensure that the composite material and cotton fiber are evenly distributed; wet spinning the mixed spinning solution through a spinning nozzle at room temperature of 20°C; subjecting the wet-spun composite fiber to a coagulation bath treatment, and maintaining it in a dilute sodium hydroxide solution at 0°C to 20°C for 1 minute, so that the composite material forms a stable structure in the fiber; C. Heat treatment: In an inert gas nitrogen protection environment, the composite material and cotton fiber are uniformly heated at a temperature of 150°C for 10 minutes to obtain a cotton fiber based on a composite of copper tungsten alloy and graphene fiber.

[0052] (4) Test and evaluate the antibacterial, anti-mite and cooling properties of the composite cotton fiber: Test the antibacterial rate, repellency rate, thermal conductivity and fabric feel of the composite cotton fiber.

[0053] Comparative Example 1 (1) Preparation of graphene oxide fibers: Graphene oxide fibers with a diameter of 30 microns were prepared by a wet spinning method, wherein the spinning solution for wet spinning was a dispersion of graphene oxide with a sheet diameter of 50 microns in dimethylformamide, and the concentration of graphene oxide was 11 mg / mL; the inner diameter of the spinning head was 500 microns; the coagulation bath was a mixed solution of ethyl acetate and dichloromethane in a volume ratio of 200:1, and the external heating temperature during fiber collection was 100°C.

[0054] (2) Synthesis of graphene fibers: The graphene oxide fiber is placed in a high-temperature furnace for heating and reduction at a temperature of 3000°C. After heating for 1 hour, a graphene fiber with a diameter of 30 microns is obtained.

[0055] (3) Composite of copper-graphene fiber: The graphene fiber is fixed on the negative electrode of the electroplating tank for electroplating. The positive electrode of the electroplating tank is a pure copper rod. A DC voltage of 20V is applied. The electroplating solution is a mixed aqueous solution of copper sulfate (50g / L), 98wt% concentrated sulfuric acid (10mL / L) and Triton (2mL / L). After electroplating for 2 seconds, the electroplating solution on the surface of the fiber is washed off with water and dried in a vacuum oven for 5 hours. After increasing the power supply voltage, the potential of the fiber increases, and a coating of about 8 microns is obtained, thereby obtaining a graphene-copper composite fiber.

[0056] (4) Test and evaluate the antibacterial, anti-mite and cooling properties of the composite fiber: Test the antibacterial rate, repellency, thermal conductivity and fabric feel of the composite fiber.

[0057] Comparative Example 2 (1) Preparation of graphene solution: First, 2.0L of a graphene solution with a concentration of 6g / L was dispersed by ultrasonic vibration at a temperature of 60°C for 30 minutes, and then 5g of dopamine was added to dissolve it. Then, 15g of tea polyphenols was added and stirred for 30 minutes. The mixture was allowed to stand for 2 minutes to obtain a graphene solution. 2kg of cotton cellulose was added to the graphene solution, and the mixture was stirred for 20 minutes. The mixture was then filtered to obtain a uniformly mixed graphene-cotton cellulose solution.

[0058] (2) Synthesis of graphene cotton fibers: A cotton fiber with graphene is prepared by using a mixed solution of a graphene solution and cotton cellulose through pulping, impregnation, pressing, crushing, aging, yellowing, dissolving, mixing, filtering, degassing, spinning, stretching, cutting, refining and drying processes.

[0059] (3) Test and evaluate the antibacterial, anti-mite and cooling properties of graphene cotton fibers: Test the antibacterial rate, repellency rate, thermal conductivity and fabric feel of graphene cotton fibers.

[0060] Result analysis:

[0061] From the data results of the performance comparison table of composite fibers prepared by different processes of Examples 1-6 and Comparative Examples 1-2, it can be seen that the antibacterial rate of Examples 1-6 of the present invention is greater than that of Comparative Examples 1-2, indicating that the antibacterial rate of the composite cotton fiber prepared by the present invention is high and the antibacterial performance is good; the repellency rate of each product in Examples 1-6 is smaller than that of Comparative Examples 1-2, indicating that the mite repellency rate of the composite cotton fiber prepared by the present invention is high, and the repellency values ​​of Examples 1-6 are all above 90%, indicating that the anti-mite effect of the composite cotton fiber prepared by the present invention is extremely strong; the thermal conductivity of each product in Examples 1-6 is smaller than that of Comparative Examples 1-2, indicating that the thermal conductivity of the composite cotton fiber prepared by the present invention is high; the body sense evaluation of each product in Examples 1-6 is greater than that of Comparative Examples 1-2, indicating that the body sense of the composite cotton fiber prepared by the present invention is good and the cooling effect is good. Comprehensive comparison, in the data results of Examples 1-6 and Comparative Examples 1-2, it is reflected that the present invention prepares a cotton fiber composite material with excellent composite performance by compounding copper-tungsten alloy particles and graphene fibers into traditional cotton fibers. The fiber has excellent antibacterial, anti-mite and cooling properties, while maintaining the softness and comfort of cotton fibers. It has significant market potential and application value in the fields of clothing, bedding, and medical protection. Compared with traditional processes, the preparation method of the present invention not only significantly improves the performance of composite cotton fibers, but also effectively reduces pollution and health risks, and is more friendly to the environment and human health.

Claims

1. A method for preparing antibacterial and anti-mite cool cotton fiber based on copper-tungsten alloy and graphene fiber composite, characterized in that: The following steps are involved: (1) Preparation of copper-tungsten alloy particles: Tungsten and copper are mixed in a mass ratio of 1-3:1 and made into microparticles through processes such as high-temperature melting, gas stirring, and spheroidal graphite crushing; (2) Synthesis of graphene fibers: Graphene fibers are prepared by chemical vapor deposition, copper foil is selected as a substrate, the temperature is raised to 1000°C to 1600°C in a high-temperature tube furnace for 20-30 minutes, and inert gas nitrogen is introduced for protection, the nitrogen flow rate is set to 100-200sccm, and the reaction is carried out for 40-60 minutes; the introduction of protective gas is stopped, and carbon source gas methane and hydrogen are introduced instead, and the exhaust is cooled after maintaining for 20-30 minutes, and the substrate is removed by chemical etching, the time is controlled to be 30-60 minutes, and vacuum drying is carried out at 60-80°C for 30-60 minutes to obtain graphene fibers; (3) Composite treatment of cotton fibers: Copper-tungsten alloy particles and graphene fibers are mixed in a mass ratio of 1-2:1, and ultrasonicated at 20-40 kHz in deionized water for 30 minutes to 2 hours to ensure that the two are evenly mixed. A cotton fiber based on a composite of copper-tungsten alloy and graphene fibers is obtained by wet spinning and heat treatment.

2. The method for preparing the antibacterial and anti-mite cool cotton fiber based on the composite of copper-tungsten alloy and graphene fiber according to claim 1, characterized in that: The preparation of the copper-tungsten alloy particles comprises: A. Raw material preparation: Tungsten powder and copper powder are mixed into copper-tungsten composite powder according to the proportion, and the mass ratio of tungsten powder to copper powder is 1-3:1, and the mixture is ensured to be even; B Melting and stirring: The tungsten powder and copper powder are heated to a molten state in a high-temperature furnace, the temperature is set to 1800℃ to 2000℃, and inert gas nitrogen is introduced by bottom blowing technology. The uniformity of the alloy is improved by gas stirring to maintain a stable alloy liquid molten state; C Cooling and crushing: The molten alloy liquid is rapidly cooled to form a solid alloy block; a ball mill is used to crush the cooled alloy block into nano-scale particles with a diameter between 50nm and 500nm, so as to facilitate compounding with cotton fibers.

3. The method for preparing the antibacterial and anti-mite cool cotton fiber based on the composite of copper-tungsten alloy and graphene fiber according to claim 2, characterized in that: The preparation and pulverization process of the copper-tungsten alloy particles is as follows: in a ball mill, a ball milling medium and a grinding ball are added, wherein the ball milling medium is a volatile organic solvent ethanol, which accounts for 5-10% of the mass of the copper-tungsten composite powder; the mass ratio of the grinding ball to the copper-tungsten composite powder is 50-60:1; nitrogen gas is filled into the ball mill as a protective gas, the circulating cooling water of the ball mill is turned on, and ball milling is started for 50-100 hours. After the ball milling is finished, the powder is allowed to stand for a while, and the powder is taken out after the powder and the grinding ball are fully cooled to obtain a nano-scale copper-tungsten alloy powder.

4. The method for preparing the antibacterial and anti-mite cool cotton fiber based on the composite of copper-tungsten alloy and graphene fiber according to claim 1, characterized in that: The synthesis of the graphene fiber comprises: A. Heating deposition: Copper foil is selected as the substrate, and after being washed with deionized water to remove surface impurities, it is placed in a high-temperature tube furnace and heated to 1000°C to 1600°C within 20-30 minutes, and inert gas nitrogen is introduced for protection, and the nitrogen flow rate is set to 100-200 sccm; when the temperature in the furnace stabilizes at the target temperature, the introduction of protective gas is stopped, and carbon source gas methane and hydrogen are introduced instead, and maintained for 20-30 minutes, with a methane flow rate of 10-50 sccm and a hydrogen flow rate of 100-300 sccm; B Exhaust Cooling: After the reaction is completed, the methane gas is turned off, and only the hydrogen gas is kept flowing in. The hydrogen gas is continued to be introduced to protect the graphene film from oxidation. The hydrogen gas flow rate is 100-200 sccm, and the cooling rate is controlled to be 5-10°C / min. After gradually cooling from the reaction temperature to room temperature, the hydrogen gas is turned off, and the metal foil or silicon wafer is taken out. At this time, a graphene film can be obtained on the substrate; C Etching and demolding: The substrate is removed by chemical etching, and the copper foil is etched with a dilute hydrochloric acid solution for 30-60 minutes; the etched graphene fiber is washed with deionized water for multiple times to remove residual acidic substances and metal impurities; after washing, the graphene fiber is placed in a drying oven for vacuum drying at a temperature of 60-80°C to obtain graphene fiber.

5. The method for preparing the antibacterial and anti-mite cool cotton fiber based on the composite of copper-tungsten alloy and graphene fiber according to claim 1, characterized in that: The composite treatment of the cotton fiber comprises: A. Mixing of composite materials: Copper tungsten alloy particles and graphene fibers are mixed in a mass ratio of 1-2:1, and ultrasonic dispersion technology is used to select an ultrasonic frequency of 20-40 kHz in deionized water for 30 minutes to 2 hours to ensure that the two are evenly mixed; Composite treatment of B composite materials and cotton fibers: The cotton fiber is dissolved in a sodium hydroxide solvent system to form a spinning solution; the mixed copper-tungsten alloy particle-graphene fiber composite material is gradually added to the spinning solution, and mixed with a stirrer to ensure that the composite material and the cotton fiber are evenly distributed; the mixed spinning solution is wet-spun at room temperature of 20°C-40°C through a spinning nozzle; the wet-spun composite fiber is subjected to a coagulation bath treatment, and maintained in a dilute sodium hydroxide solution at 0°C to 20°C for 1-5 minutes, so that the composite material forms a stable structure in the fiber; CHeat Treatment: In an inert gas nitrogen protection environment, the composite material and cotton fiber are uniformly heated at a temperature of 150°C to 250°C and a time of 10 minutes to 60 minutes to obtain a cotton fiber based on a composite of copper tungsten alloy and graphene fiber.

6. The antibacterial and anti-mite cool cotton fiber based on the composite of copper-tungsten alloy and graphene fiber prepared according to claim 1, characterized in that: The composite cotton fiber can be verified by performance evaluation, including: testing and evaluating the antibacterial performance, anti-mite performance and cooling performance of the composite cotton fiber, and verifying that the product is an antibacterial, anti-mite and cooling cotton fiber based on a composite of copper-tungsten alloy and graphene fiber.

7. The antibacterial and anti-mite cool cotton fiber based on the composite of copper-tungsten alloy and graphene fiber according to claim 6, characterized in that: The cotton fiber contains copper-tungsten alloy particles and graphene fibers. The mass fraction of the copper-tungsten alloy particles is 0.5%-5%, the diameter is 50nm-5μm, and they are evenly distributed; the diameter of the graphene fibers is 1μm-10μm, and the mass fraction is 0.1%-2%.

8. An application of antibacterial and anti-mite cool cotton fiber based on copper-tungsten alloy and graphene fiber composite, characterized in that: The cotton fiber is applied to clothing, bedding or medical protection fields to provide antibacterial, anti-mite and cooling functions.

Citation Information

Patent Citations

  • Preparation method of anti-bacterial and mite-proof sulfur-containing viscose fiber

    CN105113033A

  • Graphene-copper composite fiber and preparation method thereof

    CN106702732A

  • Graphene cotton fiber preparation method

    CN107034536A

  • Antibacterial and antifouling organic cotton and kapok blended yarns and preparation method thereof

    CN112481760A

  • Preparation method of antibacterial anti-mite healthy cotton fiber based on compounding of copper-silver alloy and graphene fiber

    CN119145213A